Optimization of the debutanizer in platforming unit using PRO/II - Wiwut Tanthapanichakoon (Chulalongkorn University, 2010)
To present the simulation model and the optimization of the operating conditions for the debutanizer of a platforming unit in a refinery plant using PRO/II for the most profit based on product quality constraints by varying the debutanizer column pressure and reboiler heat duty. The simulation models were simulated using PRO/II and the actual characteristic data of the debutanizer under steady state operation. The simulation results of the base case were found to agree well with the actual operating data. According to the preliminary economic evaluation by the optimization at the debutanizer column pressure of 14.5 kg/cm2 and the reboiler heat duty of 3.2364 X 10 [superscript 6] kcal/h or so-called a relaxed reformate RVP case (at max. reformate Reid vapor pressure at 60 degree F of 5.22 psi), the greatest economic benefit of 61.12 $US/h was obtained. This case was verified as a production guidelines. In addition, it was found that with an increase in the 8th-tray’s temperature, the amount of [subscript 5 superscript +] in liquefied petroleum gas (LPG) significantly increased without the effect on the reformate Reid vapor pressure at 60 degree F.